A simple self-assembly strategy for ultrahigh surface area nitrogen-doped porous carbon nanospheres with enhanced adsorption and energy storage performances. Issue 50 (9th June 2017) - Tang, Zhiwei; Liu, Shaohong; Lu, Zhitao; Lin, Xidong; Zheng, Bingna; Liu, Ruliang; Wu, Dingcai; Fu, Ruowen
Abstract : Versatile N-doped porous carbon nanospheres with ultrahigh surface areas were prepared based on copolymerization-induced self-assembly. Abstract : A class of novel N-doped porous carbon nanospheres (PCNSs) with ultrahigh surface areas ( e.g., Langmuir surface area = 3219 m 2 g −1 ) and large templated mesopore diameters (up to 18.6 nm) was synthesized based upon a simple yet efficient copolymerization-induced self-assembly process of aniline/pyrrole co-monomers and block copolymer templates. The PCNSs exhibited enhanced adsorption properties towards creatinine and superior lithium-sulfur battery performances.